Ministry of Tourism Decree No. 825 of the year 2013 regarding the provisional license of the Tourism Establishments قرار وزير السياحة رقم 825 لسنة 2013 بشأن التراخيص المؤقتة للمنشآت السياحية / Ministry of Tourism - Egypt. Ministry of Tourism (2025)
Ministry of tourism decree no. 825 of the year 2013 issued on 11/11/2013 – وزارة السياحة قرار رقم 825 لسنة 2013 صادر بتاريخ 11/11/2013